PENGGUNAAN METODE BRIEF COUNSELING UNTUK MENINGKATKAN KEPATUHAN MINUM OBAT DAN KEBERHASILAN TERAPI PASIEN HIPERTENSI DI APOTEK KHANZA FARMA GAMBUT - Muhammad Reza Fahlevi; Aulia Rahim (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2020)
Hypertension is a chronic disease that causes many deaths when handled incorrectly, characterized by blood pressure above normal values. Hypertensive patients require pharmacist intervention to achieve control of blood pressure within normal limits. The purpose of this study was to see the effect of the brief counseling method to improve medication adherence and control the blood pressure of hypertensive patients to be in the range of normal blood pressure values ​​at the Khanza Farma Pharmacy. This study used a quasi experimental design by providing 60 patients with brief counseling intervention to hypertension patients. Study data from patients were followed and collected prospectively. Data collection using a questionnaire given before and after the intervention brief counseling. The exclusion criteria in this study were deaf, pregnant, illiterate, and uncooperative patients. Blood pressure data collected is pressure data taken pre and post study. Questionnaire data and blood pressure were analyzed using paired t-test and Wilcoxon. The results showed that there was a significant decrease in systolic and diastolic blood pressure in the post study (p <0.05) after gave brief counseling. Brief counseling had an effect on increasing patient adherence (p <0.05). The conclusion of this study is that there is an increase in patient adherence and a decrease in blood pressure in hypertensive patients after being given brief counseling.